THE EFFECT OF DEXAMETASONE IN REDUCING PAIN AND SWELLING AFTER ORAL SURGICAL INTERVENTIONS - Bajrami, Muhamet; Koneski, Filip; Markovska Arsovska, Mirjana; Stojanova, Irena; Gjorgjievski, Pavle (Journal of Morphological Sciences, 2023)
In case of tissue injury that leads to inflammation. Symptoms of inflammation can be prevented by careful and atraumatic workup and by anti-inflammatory drugs. Dexamethasone as an anti-inflammatory drug is very often used because of its higher potency, low sodium retention ability and longer half-life. The aim of the paper is to determine the impact of dexamethasone depending on the method of application on postoperative morbidity after surgical extraction of impacted third molars. Interventions were performed in third molars, after which ampoules of Dexamethasone 4mg were administered as an anti-inflammatory drug. In all studied groups, a statistically significant difference in the degree of pain between the two time intervals was found for p<0.05, i.e. pain was significantly lower on the seventh postoperative day compared to the first postoperative day in all groups. In all studied groups, a statistically significant difference in the degree of swelling between the two time intervals was found for p<0.05, i.e. swelling was significantly lower on the seventh postoperative day compared to the first postoperative day in all groups. Locally applied dexamethasone immediately after surgical intervention has a positive effect in reducing swelling and pain in the first postoperative days, resulting in faster healing of the surgical wound, and thus faster recovery of the patient's comfort. Keywords : Anti-inflammatory drug, Dexamethasone, swelling, pain. https://doi.org/10.55302/JMS2361156b